General Requirements for Technological Equipment Used in the Packaging of Livestock Products - Fayzieva Shakhnoza Doniyorovna; Pardayev Roʻziboy Gulmurod o‘g‘li (American Journal of Biodiversity, 2025)
In livestock product processing enterprises, it is essential to reduce unnecessary labor, improve working conditions, and ensure product safety by equipping facilities with high-quality packaging machines and equipment. This article presents an overview of the general requirements for packaging equipment used in the storage and processing of livestock products